Effects of lipid peroxidation products on lipofuscinogenesis and autophagy in human retinal pigment epithelial cells - Krohne, Tim Ulrich; Stratmann, Nina Kristina; Kopitz, Jürgen; Holz, Frank G. (Experimental eye research, 2010)
Several lines of evidence suggest that progressive dysfunction of the retinal pigment epithelium (RPE) is central to the pathogenesis of age-related macular degeneration (AMD). We previously demonstrated that protein modifications with lipid peroxidation products, such as 4-hydroxynonenal (HNE) and malondialdehyde (MDA), induce lysosomal dysfunction in RPE cells in vitro. Here, we investigated whether phagocytosis of modified photoreceptor outer segments (POS) affects lipofuscinogenesis and autophagy, two interrelated processes directly connected to lysosomal function. Incubation of human RPE cells with HNE- and MDA-modified POS resulted in pronounced intracellular accumulation of granular material with lipofuscin-like autofluorescence. After daily treatment with modified POS for 7 days, cellular autofluorescence increased 8.2-fold as quantified by flow cytometry. In the presence of the lysosomal inhibitor ammonium chloride, unmodified POS likewise induced an 8.0-fold increase in autofluorescence. Spectral profiles of cellular autofluorescence after incubation with modified POS were unchanged compared to incubation with native POS. Autophagy activity, measured as turnover of metabolically radiolabeled endogenous proteins, was reduced by both HNE- and MDA-modified POS by 40%. Autophagy inhibition by 3-methyladenine and lysosomal inhibition by ammonium chloride induced lipofuscinogenesis even in the absence of POS. In summary, our results demonstrate that induction of lysosomal dysfunction by lipid peroxidation-derived protein modifications results in increased lipofuscinogenesis and reduced autophagy activity in RPE cells in vitro. These mechanisms may contribute to RPE cell dysfunction and degeneration in AMD.
Gesehen am 06.03.2023